Family-school cooperation in the context of traumatic transitions in Serbian society - Polovina, Nada (International Journal about Parents in Education, 2023)
The main topic of this paper is to clarify from a point of a researcher and practitioner a complex issue of parent-school cooperation under the pressures of long lasting and traumatic transitions in Serbian society. The paper consists of two parts. The first part includes «vertical» research based analysis focused on the parallel processes of change in a broader society and family’s functioning with reflections upon new meanings and potentials for parent involvement in academic socialization of their children. In the discourse of leading sociological and socio-psychological researches conducted during the last ten years, parental position and their potentials are described with the following words: confusion, stress, material deprivation, collapse and demoralization of family life, short-term adaptation strategies in rapidly changing environment, time and energy draining and lack of physical and psychological presence in the life of their children. The second part of the paper deals with «horizontal» research based analysis  focused on actual and concrete manifestations of parent-school cooperation, parent’s needs and resources connected to elementary and secondary level of their children’s schooling. Leading psycho-pedagogical quantitative, qualitative and action-based researches conducted during 2006 are presented, with the aim of analyzing the actual state of functioning and identifying systemic knots that support, hamper or block family-school cooperation. Words like disengagement, passivesation, tension and dissatisfaction, pseudo-cooperation, decreasing of parental and school authorities, are emphasized in the discourse of this group of research. Finally, the author integrates two levels of analysis and suggests ways of improving the quality of parent engagement in school/education.